An ionic liquid route to prepare copper sulphide nanocrystals aiming at photocatalytic applications. Issue 41 (8th April 2016) - Estrada, Ana C.; Silva, Fábio M.; Soares, Sofia F.; Coutinho, João A. P.; Trindade, Tito
Abstract : Copper sulphide nanocrystals of different phases and exhibiting distinct optical properties have been prepared via thermolysis of single-molecule precursors in ionic liquids aiming at photocatalytic applications. Abstract : Copper sulphide crystallizes in a variety of phases that exhibit distinct optical properties including different optical band gaps in the visible region. The crystalline phases are associated with unique properties shown by semiconductor nanocrystals that could be exploited to produce new photocatalysts with tuned optical behavior. This research reports on the use of ionic liquids as a reaction medium to produce copper sulphide nanocrystals whose crystalline phase depends on the synthesis conditions. Noteworthy, these solvents allow the production of water dispersible copper sulphides following the thermal treatment of Cu(ii ) alkyldithiocarbamates complexes, used here as single-molecule precursors, thus improving their potential for heterogeneous photocatalysis in the aqueous phase. Finally, the ensuing copper sulphides have been preliminarily assessed for their photocatalytic activity in the degradation of rhodamine B (RhB). The results indicate that the ionic liquid route described here has an impact on the copper sulphides produced and thereby on their performance as photocatalysts.